Insulin and IGF-1 signalling: longevity, protein homoeostasis and Alzheimer's disease. (20th July 2012) - O'Neill, Cora; Kiely, Aoife P.; Coakley, Meghan F.; Manning, Sean; Long-Smith, Caitriona M.
Abstract : The quality control of protein homoeostasis deteriorates with aging, causing the accumulation of misfolded proteins and neurodegeneration. Thus, in AD (Alzheimer's disease), soluble oligomers, protofibrils and fibrils of the Aβ (amyloid β-peptide) and tau protein accumulate in specific brain regions. This is associated with the progressive destruction of synaptic circuits controlling memory and higher mental function. The primary signalling mechanisms that (i) become defective in AD to alter the normal proteostasis of Aβ and tau, and (ii) initiate a pathophysiological response to cause cognitive decline, are unclear. The IIS [insulin/IGF-1 (insulin-like growth factor 1)-like signalling] pathway is mechanistically linked to longevity, protein homoeostasis, learning and memory, and is emerging to be central to both (i) and (ii). This pathway is aberrantly overactivated in AD brain at the level of increased activation of the serine/threonine kinase Akt and the phosphorylation of its downstream targets, including mTOR (mammalian target of rapamycin). Feedback inhibition of normal insulin/IGF activation of the pathway also occurs in AD due to inactivation of IRS-1 (insulin receptor substrate 1) and decreased IRS-1/2 levels. Pathogenic forms of Aβ may induce aberrant sustained activation of the PI3K (phosphoinositide 3-kinase)/Akt signal in AD, also causing non-responsive insulin and IGF-1 receptor, and altered tau phosphorylation, conformation and function. Reducing IIS activity in animal models by decreasing IGF-1R levels or inhibiting mTOR activity alters Aβ and tau protein homoeostasis towards less toxic protein conformations, improves cognitive function and extends healthy lifespan. Thus normalizing IIS dysfunction may be therapeutically relevant in abrogating Aβ and tau proteotoxicity, synaptic dysfunction and cognitive decline in AD.